Determination of entities by administrative and legal means - Колпаков, Валерій Костянтинович; Калюжний, Ростислав Андрійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
Scientific review of the monograph of P.S. Lyutikov "Phenomenon of entities as subjects of administrative law."